FEMALE GENITAL MUTILATION AND THE DEVELOPMENT OF THE GIRL CHILD IN AKPABUYO LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA - NNANA OKOIOFEM; JULIANA JEROME ADIE; OMINI UBI UBI; RUNYI DANIEL JAMES (International Studies Journal)
The main thrust of this study was to examine female genital mutilation and the development of the girl child in Akpabuyo Local Government Area of Cross River State, Nigeria. The specific objective of the study was to: examine female genital mutilation (FGM) and psychological development of the girl child in Akpabuyo LGA; explore female genital mutilation (FGM) and social development of the girl child in Akpabuyo LGA. and to ascertain how female genital mutilation (FGM) affects physical development of the girl child in Akpabuyo LGA. The variables under the specific objectives of the study were further used to form the research questions and hypotheses. Extant literatures were reviewed in line with the topic under study. The social learning and symbolic interactionism theories were used as the theoretical framework for this study. The study adopted survey research design where research questionnaire was used as the main instrument of data collection. The questionnaire containing 3 items questions designed in both open and closed ended questions and administered to the respondents. 120 questionnaires were administered and 20 were invalid while 100 valid questionnaires were used for the analysis. Comprising of 50 males and 50 females, who were selected from the projected population of 2016 in the study area, twenty respondents each were selected from five wards using the simple random samplings. The two null hypotheses were rejected, two hypotheses were tested at 0.05 level of significance thus revealing that; there is a significant relationship between female genital mutilation and psychological development of the girl child, there is a significant relationship between female genital mutilation and social development of the girl child, and there is a significant relationship between female genital mutilation in the study area. Based on the findings of the study, it was recommended amongst others that there is need for public enlightenment programmes by social workers to combat mass ignorance as well as public and intense awareness on psychological, social and physical health of the female children as well as severe penalty for those still involved in the practice of female genital mutilation in our society.